THE INFLUENCE OF TYPES AND ACT OF CHILDBIRTH ON THE RISK OF POST PARTUM DEPRESSION - Aliesya Patricia Wulandari; Dini Latifatun Nafi'ati (Journal of Psychiatry Psychology and Behavioral Research, 2022)
Depression that occurs postpartum is known as postpartum depression. In general, there is a 10-20% chance of developing postpartum depression in postpartum mothers. The incidence of postpartum depression in Indonesia ranges from 50-70% in postpartum mothers. Postpartum depression is a mood disorder that occurs after childbirth and reflects the psychological dysregulation that is a sign of major depression symptoms. There are several studies that prove that the occurrence of postpartum depression is often associated with side effects experienced by mothers during pregnancy, childbirth, or experiences of mothers with babies. Regarding obstetric causative factors, medical action is one of the factors that influence the psychological adaptation of postpartum mothers. The type of delivery affects the risk of postpartum depression due to the unpleasant experiences of the mother during childbirth. In the type of normal delivery, there are several factors that increase the risk of postpartum depression, such as prolonged labor, pain during labor, labor with device assistance and interventions in labor. In addition, the type of cesarean section delivery is a strong predisposing factor for the occurrence of postpartum depression childbirth with tool-assisted measures and interventions in childbirth. In addition, the type of cesarean section delivery is a strong predisposing factor for the occurrence of postpartum depression childbirth with tool-assisted measures and interventions in childbirth. In addition, the type of cesarean section delivery is a strong predisposing factor for the occurrence of postpartum depression.